Decentralized optimal PID controller based on characteristic matrix eigenvalues and Lyapunov function for load frequency control in KHOZESTAN area - Hamedrahmat, E.; Yazdizadeh, A.; Ramezani, M. H. (2011 6th IEEE Conference on Industrial Electronics and Applications, 2011)
One of the most important subjects in electric power systems is load frequency control (LFC) problem. In practice LFC systems use simple proportional-Integral (PI) controllers. However, since the PI controller parameters usually are tuned based on classical or trial and error approaches, they are unable to obtain good dynamic behavior against various load changes and operating conditions. In this paper a new decentralized optimal PID controller based on characteristic matrix eigenvalues and lyapunov equation is proposed as an appropriate technique for load frequency control problem. In this method, the tuning of PID controller is stated as an optimization problem which in that the Lyapunov quadratic index with respect to the variable operating condition is minimized with constraints on eigenvalues. Proposed technique is applied to a control area which is linked to other control areas of an interconnected power system. This control area includes the model of Karoon3 and Dez hydro power plant in KHOZESTAN (in south of Iran).